2020
DOI: 10.3389/fmicb.2020.00115
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Dynamics of Hepatitis E Virus Infection in Foxes (Vulpes vulpes) in Federal State of Brandenburg, Germany, 1993–2012

Abstract: Hepatitis E virus (HEV) is the main course for acute hepatitis in humans throughout the world. Human associated genotypes 1 and 2 as well as zoonotic genotypes 3 and 4 are grouped in the species Orthohepevirus A. In addition, a large variety of HEV-related viruses has been found in vertebrates including carnivores, rats, bats, and chickens, which were classified in species Orthohepevirus B-D. In 2015, partial genome sequences of a novel hepevirus were detected in feces of red foxes (Vulpes vulpes). However, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The phylogenetic analysis supports the aforementioned results. Based on the phylogeny ( Figure 1 ), our sample clustered with the cvHEV group, including the European common vole-hepeviruses rather than the novel HEV strain recently described from foxes in Germany (accession number: MN563782) [ 9 ]. Thus, suggesting that our sample contained cvHEV DNA originated from common voles ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The phylogenetic analysis supports the aforementioned results. Based on the phylogeny ( Figure 1 ), our sample clustered with the cvHEV group, including the European common vole-hepeviruses rather than the novel HEV strain recently described from foxes in Germany (accession number: MN563782) [ 9 ]. Thus, suggesting that our sample contained cvHEV DNA originated from common voles ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, a Syrian brown bear ( Ursus arctos syriacus ) in a German zoo was PCR positive for Rat-HEV without any disease symptoms, and serological evidence of Hepatitis E virus infection was confirmed in this animal, assumed a spillover infection of Rat-HEV from free-living Norway rats [ 3 ]. Recently, Eiden, et al [ 9 ] performed serological studies, where the high antibody prevalence of the virus demonstrated endemic HEV infections within a fox population in Germany, furthermore HEV genome sequence was reported in one case, also clustered to the Orthohepevirus C group. Since it is unknown if HEV associated clinical signs in foxes, it is assumed that they can be reservoir hosts for the virus [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations